Agent‐based production planning support system - Parshutin, Serge; Borisov, Arkady (Technological and Economic Development of Economy, 2010)
Production planning is the main aspect for a manufacturer affecting the income of a company. Correct production planning policy chosen for the right product at the right moment in the product life cycle (PLC) reduces production, storing and other related costs. This leads to such problems to be solved as defining the present PLC phase of a product and also determining the transition point – a moment of time when the PLC phase changes. The paper presents the Agent‐Based Production Planning Support system meant for supporting a production manager in his/her production planning decisions. The developed system is based on the analysis of historical demand for products and on the information about transitions between phases in life cycles of those products. The system creates a model and uses it to forecast a transition point for a product that only begins its life on the market. The architecture of the developed system is presented and an analysis of testing on real‐world data results is given. Article in English. Agentinė gamybos planavimo paramos sistema Santrauka. Gamybos planavimas – pagrindinis aspektas, nuo kurio priklauso bendroves pajamos. Teisingos gamybos planavimo politikos pasirinkimas konkretaus gaminio gyvavimo ciklo (GGC) metu mažina gamybos, sandeliavimo ir kitas išlaidas. Reikia nustatyti esama gaminio gyvavimo ciklo etapą ir perėjimo tašką – laiko momentą, kai pasikeičia gyvavimo ciklo etapas. Pateikiama agentinė gamybos planavimo paramos sistema, skirta gamybos vadovo planavimo sprendimams pagrįsti. Sukurtoji sistema pagrista retrospektyvine produktų paklausos analizę ir informaciją apie tų produktų gyvavimo ciklo fazių pokyčius. Sistema kuria modelį ir taiko jį prognozuojant produkto, kuris tik pradeda savo gyvavima rinkoje, perėjimo tašką. Pateikiama sukurtos sistemos struktūra ir bandymų su realiais duomenimis analizes rezultatai. Reikšminiai žodžiai: agentai, duomenų gavimas, sprendimų parama, gamybos planavimas, produkto gyvavimo ciklas, perėjimo tašku prognozavimas. First published online: 10 Feb 2011